El realismo mágico en Chabrol Algunas reflexiones sobre la película La1comedia del poder y el caso colombiano* Magical Realism in Chabrol’s Work Some Thoughts on the Film: “Comedy of Power” and the Colombian Case O realismo mágico Chabrol Algumas reflexõe (2012)
This article aims to reflect, from the movie “The comedy of power” (Chabrol, 2005) on the idea proposedby Professor Carlos Gaviria Díaz to understand the Colombian Constitution as a set of mirrors, regardingthe celebration of the twenty years of the 1991 Constitution. To this purpose, the author will take the reflectionsof some constitutionalists who have tried to analyze the relationship of asymmetry between theConstitution and reality, an evident gap in countries like Colombia. Also, from that idea, she will analyzesome of the issues highlighted in the film, such as the role of the judges in cases of corruption and societyunderstood as a set of power relations.The idea of thinking, from the film, about these topics of interest to different areas of law arises, first, fromthe concept of “empathy” proposed by some authors such as Richard Rorty and Martha Nussbaum, whohave referred to this notion as an indispensable means for the realization of rights, understood as the abilityto put yourself in the place of another. Here, turning to the cinema to reflect on law is consistent with theidea proposed by the movement “Cinema and law”: the cinema, as an art, builds empathy, produces reviewsand therefore, can be used to reflect and demonstrate through its own narratives different legal truths.